ANALISIS HUBUNGAN PERSEPSI KARYAWAN TERHADAP PROGRAM K3 DENGAN STRESS KERJA SEBAGAI VARIABEL INTERVENING - Najib, Muhammad Ainun; Puspita, Asri Dwi (JISO : Journal of Industrial and Systems Optimization, 2021)
PT. X is a manufacturing company that is engaged in smelting, metal rolling and producing products in the form of iron and concrete in the implementation of its production. This research was conducted to determine how much influence the perception of the work environment has on work stress, perceptions of workload on work stress, perceptions of work accidents on work stress, and how much influence work stress has on occupational safety and health programs for employees of PT. X Data analysis in this study uses the Partial Least Square – Structural Equation Modeling (PLS – SEM) approach with SmartPLS 3 software as an analytical tool. The first hypothesis is that the work environment variable (X1) on work stress (Y1) gets a T-count value of 2.134 with significant 0.033 <0.05. The first hypothesis of the workload variable (X2) on work stress (Y1) gets a T-count value of 0.178 with a significant value of 0.074> 0.05. The first hypothesis of the work accident variable (X) on work stress (Y1) got a T-count value of 2.957 with a significant value of 0.003 <0.05. The first hypothesis of the work stress variable (Y1) on the K3 Program (Y2) got a T-count value of 42.411 with a significant value of 0.000 <0.05.AbstrakPT. X adalah suatu perusahaan manufaktur yang berkecimpung di sektor peleburan, pengerolan logam dan menghasilkan produk berupa besi beton dalam pelaksanaan produksinya penelitian ini dilakukan untuk mengetahui seberapa pengaruh persepsi lingkungan kerja terhadap stres kerja, persepsi beban kerja terhadap stress kerja, persepsi kecelakaan kerja terhadap stress kerja, dan Seberapa besar pengaruh stress kerja terhadap program keselamatan dan kesehatan kerja pada karyawan PT. X Analisis data pada penelitian menggunakan pendekatan Partial Least Square – Structural Equation Modeling (PLS – SEM) dengan software SmartPLS 3 sebagai alat bantu analisis Hipotesis pertama variabel lingkungan kerja (X1) terhadap stress kerja (Y1) mendapat nilai T-hitung sebesar 2,134 dengan nilai signifikan 0,033<0,05. Hipotesis pertama variabel beban kerja (X2) terhadap stress kerja (Y1) mendapat nilai T-hitung sebesar 0,178 dengan nilai signifikan 0,074>0,05. Hipotesis pertama variabel kecelakaan kerja (X) terhadap stress kerja (Y1) mendapat nilai T-hitung sebesar 2,957 dengan nilai signifikan 0,003<0,05. Hipotesis pertama variabel stress kerja (Y1) terhadap Program K3 (Y2) mendapat nilai T-hitung sebesar 42,411 dengan nilai signifikan 0,000<0,05.